Enhanced bioactivity of titanium-coated polyetheretherketone implants created by a high-temperature 3D printing process. (22nd August 2019) - Jung, Hyun-Do; Jang, Tae-Sik; Lee, Ji Eun; Park, Seong Je; Son, Yong; Park, Suk-Hee
Abstract: Polyetheretherketone (PEEK), one of the potential alternatives to metallic materials for implants, necessarily involves high temperature process conditions to be three-dimensionally (3D) printed. We developed a 3D printing setup equipped with thermally stabilized modules of the printing nozzle and building chamber, by which the PEEK implants could be successfully manufactured. Under optimized printing conditions, the maximal mechanical strength of the 3D printed sample attained over 80% of the original bulk property of PEEK. To enhance the interfacial biocompatibility, the as-printed implants were postprocessed with titanium (Ti) sputtering. The Ti-coated surfaces were evaluated through characterization studies of x-ray diffraction spectra, microscopic topographies, and wetting properties. For the in vitro tests, preosteoblasts were cultured on the developed PEEK-Ti structures and evaluated in terms of cell adhesion, proliferation, and osteogenic differentiation. In addition, the bone regeneration capability of the PEEK-Ti implants was confirmed by animal experiments using a rabbit tibia defect model for a period of 12 weeks. In the overall in vitro and in vivo tests, we confirmed the superior bioactivities of the Ti-modified and 3D printed interface by comparisons between the samples of machined and printed samples with or without Ti coating. Taken together, the comprehensive manufacturing approaches that involve 3D printing and biocompatible postprocessing are expected to have universal applicability in a wide range of bone tissue engineering.